User Satisfaction In Outpatient Gynecology Service In The National Maternal Perinatal Institute - Ochante-Rementería, Jovanna (2019)
Objectives. Determine the level of user satisfaction in outpatient gynecology. Materials and methods. Observational, descriptive, retrospective and cross-sectional study. Survey structured for 126 patients ranging from 19-65 years old attended in Outpatient Gynecology at the National Maternal and Perinatal Institute.